Dissecting genetic variation and association mapping for agro-morphological traits under high temperature stress in pea (Pisum sativum L.) - Zanetta, Chindy Ulima; Gali, Krishna Kishore; Rafii, Mohd Y.; Jaafar, Juju Nakasha; Waluyo, Budi; Warkentin, Thomas D.; Ramlee, Shairul Izan (Springer Science and Business Media, 2024)
High temperature stress is a severe problem that limits the productivity of pea and most crops. Investigating the genetic basis of agronomic and morphological traits related to heat stress tolerance could expedite the development of stress-adaptive pea cultivars, thereby increasing productivity for food security. This study aimed to explore genetic variation in Southeast Asia pea accessions and identify marker-trait associations (MTAs) related to heat stress. Phenotypic data were assessed for genetic variation in 11 traits including phenological, morphological, and agronomic, under high temperature conditions in Malaysia and Indonesia. A collection of 94 pea accessions of 92 landraces from Indonesia and two commercial cultivars from Taiwan was used for genome-wide association study. A total of 1,974 high-quality single nucleotide polymorphisms (SNPs) were used to determine marker-trait associations. Population structure, principal coordinate analysis, and kinship analysis revealed that the accessions could be divided into three groups. The BLINK model identified twenty-six significant (P ≤ 0.001) MTAs for the observed characters across all locations and consistent in multiple individual locations. Two SNPs on Chr2 and Chr6 that were associated with more than one trait predicted to co-localize with a gene involved in mediating environmental stress responses and may provide a novel mechanism of heat tolerance in pea. Nineteen candidate genes were identified within 15 kb distance of 26 significant SNPs associated with days to flowering, number of nodes, peduncle length, days to harvesting green pod, days to physiological maturity, and seed volume. The SNP markers and candidate genes identified in this study have potential for marker-assisted selection toward rapid development of pea cultivars with improved heat tolerance. © 2024, The Author(s), under exclusive licence to Springer Nature B.V.